Implikasi Program Bimbingan Konseling dalam Meningkatkan Kedisiplinan Siswa di MI Bina Ihsan Mulia Badung Tahun Pelajaran 2019/2020 - Rusdi, Moh; Jumari, Jumari; Hidayat, Tauhid (Faidatuna, 2022)
Counseling guidance is a relief effort given to students in order to obtain self-concept and self- confidence, to be used by students in fixing problems that exist in students. The purpose of this research is to find out 1) How is the implementation of counseling guidance program at MI Bina Ihsan Mulia Badung 2019/2020 Learning Year, 2) How is the student discipline in MI Bina Ihsan Mulia Badung 2019/2020 Learning Year, 3) How is the implementation of the guidance program counseling in improving discipline in MI Bina Ihsan Mulia Badung 2019/2020 Academic Year? The type of research uses a qualitative approach that is descriptive. Resource persons in this study are the principal, class teacher, student field. Data collection techniques used were interviews, observation, and documentation. Data analysis is performed interactively, starting from data reduction, data presentation, and drawing conclusions. Based on the results of the application of counseling guidance in MI Bina Ihsan Mulia Badung conducted by the homeroom teacher, subject teacher, and school principal. The counseling guidance program in MI Bina Ihsan Mulia Badung is provided with an information service orientation service for individual counseling services for mediation services.